Surface and Catalytic Properties of the CoO/MgO System Doped with AgO and MoO - A.M. Ghozza (Adsorption Science & Technology)
The effects on their surface and catalytic properties of doping 0.2Co 3 O 4 /MgO solids with Ag 2 O or MoO 3 (0.2–1.0 wt%) were investigated using nitrogen adsorption at −196°C, the oxidation of CO by O 2 at 200–250°C and the decomposition of H 2 O 2 at 30–50°C. The results revealed that doping the investigated system followed by calcination at 500–900°C brought about a progressive increase in the specific surface area to an extent proportional to the amount of dopants added. This led to an increase in the catalytic activities of the doped solids towards H 2 O 2 decomposition, especially for solids calcined at 700°C and 900°C. However, this increase was more pronounced with MoO 3 doping. On the other hand, the catalytic activity of the investigated system in CO oxidation by O 2 expressed as the reaction rate constant per unit surface area (k̅) was found to decrease on increasing the amount of Ag 2 O and MoO 3 added. Calcination of the investigated system at 900°C led to the effective dissolution of most of the cobalt oxide added into the MgO lattice to yield a CoO-MgO solid solution. Doping 0.2Co 3 O 4 /MgO solid followed by heating at 500, 700 and 900°C did not alter the mechanism of the catalytic reaction but increased the concentration of Co 3+ -Co 2+ ion pairs acting as active sites in the process.